Irrigation, Nutrition, and Citrus Fruit Quality: SL 207/SS426, rev. 4/2018 - Zekri, Mongi; Obreza, Thomas A.; Koo, Robert; Alferez, Fernando M. (EDIS, 2018)
This 3-page publication targets agricultural and horticultural producers, homeowners, Extension agents, industry or governmental staff, land managers, other professionals, youth and interested citizens. It is a minor revision written by Mongi Zekri, Thomas A. Obreza, Robert Koo, and Fernando M. Alferez, and published by the Soil and Water Science Department, April 2018. SL 207/SS426: Irrigation, Nutrition, and Citrus Fruit Quality (ufl.edu)